A Systematic Review of Food Safety Risks in Plant and Seaweeds as Emerging Alernative Protein Sources - Leila Mehdizadehtapeh; Elena Bancalari; Delia Grace; Parag Acharya; Maria Paciulli; Marcello Alinovi; Giovanni Sogari; Tanya Stathers; Said Ennahli; Sümeyye Uçak; Marwa Tainsa; El Amine Ajal; Serap Andaç; Ahmad Nimatullah Al-Baarri; İsmail Hakkı Tekiner (Diponegoro University, 2025)
Alternative plant and seaweed protein sources other than soy and pea have gained significant interest as sustainable replacements of animal proteins in the last decades. However, despite a large food safety literature base, there are concerns about their food safety risks. The current study aims to synthesize the existing knowledge and gaps on safety risks associated with brewers' spent grain (BSG), grapes, hazelnuts, potatoes, pumpkins, and seaweed. A systematic review between 2003 and 2023 was conducted in the PubMed database to identify microbial, chemical, mycotoxins, heavy metals, and allergenic risks in the key commodities. The records obtained were exported into an online reference management platform, screened by inclusion and exclusion search strings, and the duplicates were removed. Finally, two reviewers assessed the eligibility of the full-text articles. The findings demonstrated that 9127 papers were identified, and 1639 of them were left for eligibility assessment. The reviewers finally included 144 articles. Amongst the commodities, the most safety studies were on grapes, with 55 papers, followed by potatoes (n=38), seaweed (n=21), hazelnuts (n=19), pumpkin (n=9), and BSG (n=2), respectively. Based on the risk type, heavy metals were the most studied ones, with 49 papers, followed by mycotoxins (n=31), microbial risks (n=23), chemical contaminants (n=21), and allergenic risks (n=20), respectively. To meet the growing need for plant and seaweed proteins, their food safety aspects should be extensively studied to deliver safe, healthy, and affordable substitutes based on robust safety standards.